Variation for N Uptake System in Maize: Genotypic Response to N Supply - Garnett, Trevor; Plett, Darren; Conn, Vanessa; Conn, Simon; Rabie, Huwaida; Rafalski, J. Antoni; Dhugga, Kanwarpal; Tester, Mark A.; Kaiser, Brent N. (Frontiers in Plant Science, 2015)
An understanding of the adaptations made by plants in their nitrogen (N) uptake systems in response to reduced N supply is important to the development of cereals with enhanced N uptake efficiency (NUpE). Twenty seven diverse genotypes of maize (Zea mays, L.) were grown in hydroponics for three weeks with limiting or adequate N supply. Genotype response to N was assessed on the basis of biomass characteristics and the activities of the nitrate (NO3-) and ammonium (NH4+) high-affinity transport systems. Genotypes differed greatly for the ability to maintain biomass with reduced N. Genotypes that maintained biomass at reduced N maintained net N uptake with no change in size of the root relative to the shoot. The root uptake capacity for both NO3- and NH4+ increased with reduced N. Transcript levels of putative NO3- and NH4+ transporter genes in the root tissue of a subset of the genotypes revealed that is was predominately putative ZmNRT2s whose transcript levels responded to N treatments. The correlation between the ratio of transcripts of ZmNRT2.2 between the two N levels and a genotypes ability to maintain biomass with reduced N suggests a role in enhancing N uptake efficiency. The observed variation in the ability to capture N at low N provides scope for both improving NUpE in maize and also to better understand the N uptake system in cereals.